2008
DOI: 10.1177/147323000803600411
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Protein Expression of VEGF-C, MMP-2 and Lymph Node Metastasis in Papillary Thyroid Cancer

Abstract: Papillary thyroid cancer (PTC) is a common malignancy and has a good prognosis after appropriate treatment. PTC cells spread mainly by lymph node metastasis (LNM), but the mechanism is not well understood. Expression of vascular endothelial growth factor C (VEGF-C) and matrix metalloproteinase 2 (MMP-2) protein was studied immunohistochemically from the archived specimens of 65 PTC patients who initially presented without LNM. In this retrospective study, the frequency of expression differed significantly betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…VEGF-C and VEGF-D have previously been shown to be related to lymph node metastasis in patients with DTC (18)(19)(20)(21). Although lymphangiogenesis is thought to be mediated by VEGFR-3, this study demonstrated a relation between the expression of VEGFR1 and lymph node metastasis in DTC.…”
Section: Discussionmentioning
confidence: 59%
“…VEGF-C and VEGF-D have previously been shown to be related to lymph node metastasis in patients with DTC (18)(19)(20)(21). Although lymphangiogenesis is thought to be mediated by VEGFR-3, this study demonstrated a relation between the expression of VEGFR1 and lymph node metastasis in DTC.…”
Section: Discussionmentioning
confidence: 59%
“…However, these markers do not appear to discriminate between PTC with and without nodal metastases. In the small body of work examining metastatic PTC disease, 2 small cohorts demonstrated that vascular endothelial growth factor-C (VEGF-C), metallomatrix proteinase 2, and basic fibroblast growth factor (bFGF) were expressed more frequently in PTC primary tumors with nodal metastases, but the nodal deposits were not surveyed [27,28]. Previous studies examining cell cycle markers in benign, malignant, and metastatic thyroid neoplasms demonstrated that cyclin D1, cyclin E1, p16, p21, and p27 were expressed at higher levels in PTC primary tumors [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in VEGF mRNA may serve as an adaptive response to the reduced oxygen availability. Increased VEGF expression will promote angiogenesis in tumors and facilitate tumor aggressiveness and metastasis [58][59][60].…”
Section: Discussionmentioning
confidence: 99%